Taking Care of the Puerto Rican Patient: Historical Perspectives, Health Status, and Health Care Access - Débora H. Silva Díaz; Glenn Garcia; Camille Clare; Julia Su; Erica Friedman; Renee Williams; Juan Vazquez; John Paul Sánchez (Association of American Medical Colleges, 2020)
Introduction Hispanics are the largest minority group in the US at 18% of the population, of which Puerto Ricans are the second largest subgroup. Puerto Ricans have poorer health status than other US Hispanic and non-Hispanic populations. Thus, health care providers need to know about and distinguish the health care problems of Puerto Ricans to improve their health. Although there are some published curricula addressing how to provide health care to Hispanic populations, none address the specific needs of Puerto Ricans. Methods We developed a 60-minute interactive workshop consisting of a PowerPoint presentation and case discussion aimed at increasing health care providers' knowledge and understanding of the historical perspective that led to Puerto Rican identity, health issues and disparities, and the health care access problems of mainland and islander Puerto Ricans. Evaluation consisted of pre- and postworkshop questionnaires. Results There were a total of 64 participants with diverse ethnoracial identities including medical students, residents, faculty, physicians, researchers, administrators, and students/faculty from nursing, occupational therapy, genetic counseling, biomedical sciences, and social work programs. A comparison of pre- and postworkshop data showed a statistically significant increase in participants' confidence in meeting all learning objectives. Participants positively commented on the interactive nature of the workshop, the case discussion, and the historical perspective provided. Discussion With the increasing migration of Puerto Ricans to the US mainland this module can uniquely improve the preparation of current and future health care providers to provide competent care to Puerto Rican patients.